Effect of ethyl alcohol extract of fenugreek seeds Trigonella foenum graecum in the destruction of the different stages of the insect beetle rust-red flour Tribolium casteneum (Coleoptera: Tenebrionidae) (Walker)* - السامرائي, اشواق حسام; هلال, سعدي محمد; رشيد, كريم حميد (Journal of Kerbala for Agricultural Sciences, 2015)
A series of laboratory experiments were carried out to reveal the effect of ethyl alcohol extracts of Trigonella foenum- graecum seeds against different stages of Tribolium castaneum (Herbst), using different methods of spraying . The number of larvae emerged from infected flour with eggs of T. castaneum was 0.33 at 5% concentration as compared with 18.00 in the control treatment . The mortality percentage of early stage of larvae was 90% 90% and 90% when seed extract was applied to insect either directly or on their food or by sprying the surfaces of the rearing container , respectively. The percentage of late larval instar were 90% , 90% and 81.14% when ethyl alcohol extract sprayed on larvae directly ,or on their food or on surfaces of container. Respectively. The pupa mortality percentage was 90% while adult mortality percentage was 90% and 90% and 90% when the extract was either spray direct or their food or on surface of rearing container